2021
DOI: 10.1113/jp281535
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic, proteomic and phosphoproteomic underpinnings of daily exercise performance and zeitgeber activity of training in mouse muscle

Abstract: support-information-section). Key pointsr Maximal endurance performance is greater in the early daytime. r Timed exercise differentially alters the muscle transcriptome and (phospho)-proteome. r Early daytime exercise triggers energy provisioning and tissue regeneration. r Early night-time exercise activates stress-related and catabolic pathways. r Scheduled training has limited effects on the muscle and liver circadian clocks.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 93 publications
5
35
1
Order By: Relevance
“…4E), three (Pgm1-Ser 117 , Pgm1-Thr 115 , Pgm1-Thr 19 ) were increased at the pre timepoint 1.7-, 3-, and 5.5-fold, respectively. Phosphorylation levels on these sites were then uniformly decreased immediately following exercise (similar to recent findings in exercised rodents - Maier et al 2021), followed by a sharp increase at the 1hrp timepoint - all of which were greater in the cavefish (Fig 4E and 4F). These findings indicate that in both basal and recovery states, cavefish have hyperphosphorylation of Pgm1 relative to surface fish - suggesting phosphorylation of Pgm1 is a crucial node in cavefish glycogen metabolism.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…4E), three (Pgm1-Ser 117 , Pgm1-Thr 115 , Pgm1-Thr 19 ) were increased at the pre timepoint 1.7-, 3-, and 5.5-fold, respectively. Phosphorylation levels on these sites were then uniformly decreased immediately following exercise (similar to recent findings in exercised rodents - Maier et al 2021), followed by a sharp increase at the 1hrp timepoint - all of which were greater in the cavefish (Fig 4E and 4F). These findings indicate that in both basal and recovery states, cavefish have hyperphosphorylation of Pgm1 relative to surface fish - suggesting phosphorylation of Pgm1 is a crucial node in cavefish glycogen metabolism.…”
Section: Resultssupporting
confidence: 84%
“…2K). These findings support our recent discovery of Tinaja, Pachón, and Molino cavefish encoding a truncated variant of Period 2 -affecting its inhibitory pparγ-binding domain -a variant we validated is present in cavefish skeletal muscle (Xiong et al 2021). Congruently, cavefish muscle had elevated expression of the lipid metabolism genes adiponectin b (adipoqb), ceramide synthase 4-b (cers4b), adiponutrin (pnpla3), and leptin receptor (lepr) (Fig.…”
Section: Cavefish Show Increased Expression Of Genes Involved In Skel...supporting
confidence: 87%
See 2 more Smart Citations
“…Given the significant impact of genetically deleting both of the circadian repressors Cry1 and Cry2 on maximum treadmill running speed in mice [17], we hypothesized that maximum sprint speed may depend on the time of day. Others have reported that sedentary male mice exhibit enhanced sprint exercise capacity early in the night when CRY1/2 protein expression is lower [6] or at the dark to light transition [25]. However, we did not detect any significant impact of time of day on maximum sprint speed in sedentary c57BL/6J male mice (Figures 1B, 1C, and S1B).…”
Section: Resultscontrasting
confidence: 62%